Good talk : a memoir in conversations - Jacob, Mira, 1973- (Random House, 2018)
"Like many six-year-olds, Mira Jacob's half-Jewish, half-Indian son, Z, has questions about everything. At first they are innocuous enough, but as tensions from the 2016 election spread from the media into his own family, they become much, much more complicated. Trying to answer him honestly, Mira has to think back to where she's gotten her own answers: her most formative conversations about race, color, sexuality, and, of course, love. Written with humor and vulnerability, this deeply relatable graphic memoir is a love letter to the art of conversation--and to the hope that hovers in our most difficult questions" --